Enantioselective Nickel-catalysed Transformations - Pellissier,Helene (Croydon : Royal Society of Chemistry, 2016)
Due to the lower costs of nickel catalysts and the high abundance of nickel complexes, enantioselective nickel-mediated transformations have received a continuous and growing attention in recent years. This book demonstrates the diversity of chemistry catalysed by chiral nickel catalysts. Discussing several different enantioselective transformations, this book presents the impressive range of uses that have been found for novel and already known nickel chiral catalysts, from basic organic transformations to completely novel methodologies including fascinating one-pot domino and multicomponent reactions. This much-needed book is ideal for researchers and industrialists in organic chemistry, synthesis and medicinal chemistry.
Keywords: Chemistry -- Physical chemistry